If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 + -6(x + 1) = 6x + 5 Reorder the terms: 3x + 9 + -6(1 + x) = 6x + 5 3x + 9 + (1 * -6 + x * -6) = 6x + 5 3x + 9 + (-6 + -6x) = 6x + 5 Reorder the terms: 9 + -6 + 3x + -6x = 6x + 5 Combine like terms: 9 + -6 = 3 3 + 3x + -6x = 6x + 5 Combine like terms: 3x + -6x = -3x 3 + -3x = 6x + 5 Reorder the terms: 3 + -3x = 5 + 6x Solving 3 + -3x = 5 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + -3x + -6x = 5 + 6x + -6x Combine like terms: -3x + -6x = -9x 3 + -9x = 5 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + -9x = 5 + 0 3 + -9x = 5 Add '-3' to each side of the equation. 3 + -3 + -9x = 5 + -3 Combine like terms: 3 + -3 = 0 0 + -9x = 5 + -3 -9x = 5 + -3 Combine like terms: 5 + -3 = 2 -9x = 2 Divide each side by '-9'. x = -0.2222222222 Simplifying x = -0.2222222222
| -8(-5m+2)=-96 | | 23g=41/2 | | 4(n-6)+10=2(n-7)-6 | | -14+3(x+10)=7(2+4)+x | | 33+3x+11x=33x | | 6+2x=3x+7+1-8 | | 5(12-3p)=1215p+60 | | -2(6-y)+4=-4 | | 9+3p-2=9p+25-4p | | x+-8=-8+3x | | 65m+50=45m+90 | | 8x+16=5x | | 90+.20x=50+.70x | | y-4x=17 | | 3x-12+4x-14=30 | | 2(2x-1)+3=9 | | 13=k/7 | | 7x-7=13+12 | | -61=d+[-18] | | 3(x+5)+3=3x+8 | | 8x-3=5+4(2x-2) | | 3-5x=10+x | | 4(-6)+10=2(n-7)-6 | | -11-7b=-7(b+2) | | -4(a-3)-(a+6)=1-8a+5+7a | | (3x-4)(2x+11)=0 | | -8+3-6x+6=-7x-2 | | 9x^2-17x-30= | | -8=-2+3/4x | | -3(4y-8)=-36 | | 30+5x+6x=30x | | 2x^4-128x=0 |